Load and recovery monitoring in Swiss top-level youth soccer players: Exploring the associations of a new web application-based score with recognised load measures - Anderegg, J. M.; Brefin, S. L.; Nigg, C. R.; Koschnick, D.; Paul, C.; Ketelhut, S. (Current Issues in Sport Science, 2024)
Introduction